Long-term dynamics of dissolved oxygen and isotopic composition in Lake Erie and Lake Ontario: Implications for eutrophication and ecosystem health - Dordoni, Marlene; Barth, Johannes; Wassenaar, Leonard I. (Journal of Great Lakes Research, 2024)
This study, focusing on Great Lakes Erie and Ontario, Canada, explores dissolved oxygen (DO) dynamics and its stable isotopic composition (δ18ODO) in the Great Lakes. Using historical dissolved oxygen data from 1965 to 2021, combined with synoptic isotopic data collected in the early 2000s, the research examined the spatiotemporal trends in DO and δ18O-DO to assess the effects of biotic and abiotic processes such as photosynthesis, respiration, and atmospheric gas exchange. The study revealed significant seasonal and depth-related variations in DO levels, with hypolimnetic hypoxia and metalimnetic oxygen minima (MOM) observed in both lakes. With its comparatively shallow depth and higher nutrient loads, Lake Erie exhibited more pronounced dissolved oxygen fluctuations, with DO levels reaching as low as 3.65 mg L−1 and δ18ODO values falling below +24.6 ‰. These findings indicated Lake Erie's more dynamic metabolic environment, particularly during the thermally stratified season. In contrast, Lake Ontario showed more stable oxygen concentration levels, with occasional dissolved oxygen depletions down to 6.80 mg L−1 and δ18ODO values up to +32.1 ‰, suggesting more localised influences of external inputs and biological processes. This study provides a long-term perspective on dissolved oxygen status in these lakes and offers essential insights into their ecological health. This work contributes valuable data for managing and protecting the Great Lakes ecosystem.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Dissolved oxygen; Dissolved oxygen isotopes (; Great Lakes; Hypolimnetic hypoxia; Lake Erie; Lake Ontario; Metalimnetic Oxygen Minimum (MOM)